Some Sufficient Conditions for Analytic Functions to Belong to 𝒬𝐾,0(𝑝,𝑞) Space - Xiaoge Meng (Abstract and Applied Analysis)
This paper gives some sufficient conditions for an analytic function to belong to the space consisting of all analytic functions 𝑓 on the unit disk such lim|𝑎|→1∫𝔻|𝑓(𝑧)|𝑝(1−|𝑧|2)𝑞𝐾(𝑔(𝑧,𝑎))𝑑𝐴(𝑧)=0.